Relacionamento entre produtividade e eficiência energética, em uma empresa gráfica - Machado, Cícero Ferreira (2017)
The measure of efficiency of the productive process is productivity, which consists of maximizing the results, using the same volume of resources or maintaining the result and reducing the volume of resources. Faced with the need to minimize environmental problems and rationalize the use of resources, the use of Energy Efficiency (EE) in the industrial sector has become an alternative to raise productivity, mainly by reducing energy losses. This work had as its general objective to analyze a relationship between productivity and energy efficiency in a graphic company in Paraíba, identifying a productivity, verifying the existing points of energy losses, evaluating the potential of energy consumption improvements and measuring the launch of Productivity and Energy Efficiency, after reducing energy losses. This work was characterized by Qualitative-Quantitative applied research, regarding the objectives of the study and descriptive. The instruments for data collection for a bibliographical research, analysis of input resources (MWh) and output (T - Production) for a calculation of productivity (T / MWh) and direct observation. After a collect of consumption, production and energy profile data, the data are tabulated and analyzed by means of the indicators, to estimate a reduction in consumption. It was verified that the productivity of the company is affected by seasonality, confirmed from the test in the F test, the coefficient of determination indicated that 63.2% of the variation of the electric energy consumption by variation of production. On the other hand, 36.8% of the variation of energy consumed cannot be explained by production, indicating that there are other process factors that do not affect production and explain consumption. As to dimensions indicated that: energy management, driving system, lighting system, cooling system and compressed air system, are responsible for 84.54% of total electricity consumption. After an evaluation of the potential for improvements, we have: energy management (6.00%), motor system (7.57%), lighting system (5.57%), refrigeration system (0.55%) and Compressed air (5.40%), corresponding to a saving of 9.39% in the company's total electricity consumption. Leading to increased productivity Gain (T / MWh) of 10.39%. In billing, a representative reduction of an annual savings of around R$ 445 thousand. It can be concluded that when there is an increase in energy efficiency, increasing productivity in a ratio, proportional, which impacts on increasing the competitiveness of the company.